The Effect of the Performance of TNI-AU Search and Rescue Team Personnel during the Cianjur Regency Earthquake Emergency Response - Moh Agus Priono; Anwar Kurniadi; Sugimin Pranoto; Pujo Widodo; Herlina Juni Risma Saragih; Kusuma Kusuma (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Earthquakes are natural phenomena that have the potential to result in physical damage and loss of life. In an emergency like this, the performance of the TNI-AU Search and Rescue team has a direct influence on the effectiveness and efficiency of rescue efforts, as happened during the earthquake emergency response period in Cianjur Regency. A quick and precise response from the TNI-AU Search and Rescue team in emergency situations such as earthquakes can have a direct impact on the safety of victims. This study aims to evaluate the ability of personnel to deal with earthquake emergency response situations in Cianjur, West Java. The research method used is a qualitative approach that involves in-depth document analysis. In general, the TNI-AU has succeeded in achieving effectiveness and efficiency in rescue efforts during the earthquake emergency response period in Cianjur Regency, including in terms of fast and appropriate victim handling, coordination with related institutions, monitoring the latest information, and the availability of equipment and defense equipment support. The results of SAR training applied by the TNI-AU have proven to provide positive results, as can be seen from direct actions taken in a short time after the earthquake.